Α-glucosidase inhibitors from Syzygium polyanthum (Wight) Walp leaves as revealed by metabolomics and in silico approaches. (10th January 2022) - Syabana, Mohamad Ana; Yuliana, Nancy Dewi; Batubara, Irmanida; Fardiaz, Dedi
Abstract: Ethnopharmacological relevance: Syzygium polyanthum (Wight) Walp leaves are traditionally used to cure diabetes in many regions of Indonesia. Traditional use involves boiling the leaves until the water is reduced to half volume, and then the decoction is taken 1–2 times daily. Despite several studies reporting the antidiabetic activity of this plant, bioactive compounds have not been well identified. Aim of the study: Indonesia is one of the countries with the highest diabetes cases, particularly type 2 diabetes mellitus (T2DM). Few people have access to modern medicinal treatment; thus, the role of antidiabetic traditional medicine has become increasingly important. This research aimed to identify α-glucosidase inhibitors from S. polyathum leaves using a metabolomics approach. When the active compounds of S. polyathum are properly identified, the quality of the herb can be more easily controlled. Materials and methods: The dried leaves of S. polyanthum were extracted by a comprehensive extraction method using a solvent combination of n-hexane, acetone, and water in a gradient, resulting in a total of 42 fractions. All fractions were subjected to an in vitro α-glucosidase inhibition test and chemical profile analysis using Nuclear Magnetic Resonance (NMR) and high performance liquid chromatography (HPLC). Orthogonal projection least square (OPLS) analysis was used to correlate the two data to identify NMR signals, and HPLC chromatogram peaks correlated to the activity. 2D NMR and ultra-high-performance liquid chromatography coupled to high-resolution mass spectrometry (UHPLC-HRMS) analyses were also used to give more precise compound identification. The activity of the identified active compounds was confirmed by an in silico technique. Results and discussion: The results of the α-glucosidase activity test showed that the most active fractions were obtained from solvents with medium polarity: Fractions 9 and 10 (F9 and F10), obtained from gradient acetone-water 4:1 and 3:2, respectively. The IC50 values of F9 and F10 were 24.8 and 31.8 μg/mL, respectively. NMR data showed that F9 had more intense and diverse signals in the aromatic region than F10. OPLS analysis results showed that some typical flavonoid signals abundant in F9 positively correlated with α-glucosidase activity. 2D NMR and UHPLC-HRMS analysis of F9 led to the conclusion that these signals could be attributed to myricetin-3-O-rhamnoside (myricitrin) and epigallocatechin-3-gallate (EGCG). In silico analysis confirmed these results, as myricitrin and EGCG had binding energies resembling acarbose as a positive control (-8.47, -8.19, and -10.13, respectively). Conclusions: NMR and HPLC-metabolomics successfully identified myricitrin and EGCG as α-glucosidase inhibitors from S. polyanthum leaves, and docking analysis validated their inhibitory activity. The results of this study justified the traditional use of S. polyanthum as an antidiabetes herbal. Graphical abstract: Image 1 Highlights: Metabolomics and in silico techniques were used to identify α-glucosidase inhibitors from Syzygium polyanthum leaf. Myricetin-3-O-rhamnoside and epigallocatechin-3-gallate were identified as α-glucosidase inhibitors of S. polyanthum leaf. In silico analysis showed that myricetin-3-O-rhamnoside and epigallocatechin-3-gallate were comparable with acarbose.